2002
DOI: 10.1021/es010199v
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disrupting Nonylphenols Are Ubiquitous in Food

Abstract: 4-Nonylphenols (NPs) are common products of biodegradation of a widely used group of nonionic surfactants, the nonylphenol ethoxylates (NPEs). These compounds are known to be persistent, toxic, and estrogen active. There is a worldwide scientific and public discussion on the potential consequences of human long term dietary exposure to such endocrine disrupters. Despite numerous determinations of NPs in environmental samples no systematical reports exist relating to concentrations of NPs in food. We analyzed N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
200
2
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(219 citation statements)
references
References 35 publications
9
200
2
8
Order By: Relevance
“…Single star p<0.05, double star p<0.01, and triple stars p<0.001 as determined by MannWhitney test might be residual detergents and disinfectants used for cleaning the filling system. Guenther et al (2002) detected estrogenic nonylphenols in a broad range of foodstuff and concluded that part of it might originate from nonionic surfactants used in cleaning agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single star p<0.05, double star p<0.01, and triple stars p<0.001 as determined by MannWhitney test might be residual detergents and disinfectants used for cleaning the filling system. Guenther et al (2002) detected estrogenic nonylphenols in a broad range of foodstuff and concluded that part of it might originate from nonionic surfactants used in cleaning agents.…”
Section: Discussionmentioning
confidence: 99%
“…The contamination of foodstuff by production-related compounds has been documented analytically. Nonylphenols, as degradation products of commercial and industrial surfactants, for example, are identified ubiquitously in a broad variety of nourishments (Guenther et al 2002).…”
mentioning
confidence: 99%
“…detergents and emulsifiers (Thiele et al, 1997;Staples et al, 1999;Guenther et al, 2002). Industrially produced nonylphenol contains about 90% of 4-nonylphenol, which consists of a mixture of branched-chain (C 9 ) isomers (Wheeler et al, 1997;Nakagawa et al, 2004;Ruß et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Isotope dilution standards (IDS) including 13 C12-BPA (ring-13 C12, 99%), and 13 C6-4-n-NP (ring-13 C6, 99%) were purchased from Cambridge Isotope Laboratories, Inc. (Andover, MA). Standards were individually dissolved in acetonitrile at concentrations ranging from 1 to 10 mg L −1 .…”
Section: Standards Reagents Chemicals and Plant Materialsmentioning
confidence: 99%
“…Nonylphenol polyethoxylates (NPEOs) are one of the most widely used classes of non-ionic surfactants, encompassing more than 80% of the world market [12]. Their biodegradation product NP has many isomers with a phenol group and a linear (4-n-NP) or branched carbon (C) chain of nine C atoms [6,13]. Widespread occurrences of BPA and NP have been reported in various contact (simulating subsurface and micro-sprinkler irrigation methods).…”
Section: Introductionmentioning
confidence: 99%